The National Library of Medicine and Interlibrary Loan - Cassidy, Thomas R. (1967)
The National Library of Medicine was a pioneer in the development of the interlibrary loan system. In 1957, the Library instituted the policy of combining loan and photocopy which it follows to this day. There has been a steady rise in the demand for photocopies from the NLM; hence, the advantage of making fuller use of local resources before approaching NLM is stressed. The criteria the Library observes to strike a balance between the national public interest expressed in the Library's statutory mission, and private interests protected by the Copyright Act, are described; but NLM will always be obliged to provide materials difficult to obtain elsewhere. Developing programs under the Medical Library Assistance Act should have considerable impact on the local availability of medical library resources.